German Design Educators' Post-Covid Challenges: Online, Artificial Intelligence (AI) and Government Data Restrictions - Fleischmann, Katja (Design and Technology Education: An International Journal, 2023)
This research examines the experiences of German design educators during the Covid-19 pandemic and explores how these experiences influenced design education's transition to the online studio two years afterwards. The research is based on surveys of 33 German design educators who represent 18 higher education institutions (University/University of Applied Sciences) during the pandemic and 32 surveys and six follow up interviews two years later. This is the first study that focuses exclusively on design education in Germany by presenting a before-and-after contextual snapshot. The results present both positive and negative experiences of educators from a wide range of design domains. The ‘offshoring’ of the studio to Internet-based communication and file sharing platforms during the pandemic has profoundly altered the perceptions and practices of design educators in Germany, where governmental hurdles, such as data restriction laws, are blocking the full integration of online technology in design education. The findings focusing on German design educator experiences are presented within the context of their international colleagues' experiences from a study conducted earlier. This research also touches on the influence of Artificial Intelligence (AI) on the future of design education as well as a general trend to go offline by encouraging a back-to-campus policy.